Retrospective study of plasma exchange in patients with idiopathic rapidly progressive glomerulonephritis and vasculitis. Issue 3 (September 1996) - Gianviti, A; Trompeter, R S; Barratt, T M; Lythgoe, M F; Dillon, M J
Abstract : A retrospective study of 48 patients was conducted to evaluate the efficacy of plasma exchange in children with idiopathic rapidly progressive glomerulonephritis (IRPGN), and renal or non-renal vasculitis. All patients were followed up at a single centre over a 15 year period. Treatment consisted of corticosteroids and/or cytotoxic agents. Plasma exchange was used in all patients because of severe renal involvement and/or clinical deterioration. One hundred per cent of patients with renal vasculitis who started plasma exchange within one month of disease onset and 58% of cases with IRPGN had significant improvement in renal function. No relapses of vasculitis were observed after treatment with plasma exchange in patients with renal and non-renal vasculitis. The results suggest that plasma exchange associated with immunosuppressive treatment could be of benefit in cases of IRPGN or vasculitis in terms of both renal and extrarenal recovery.